OPTIMIZATION MODEL IN VACCINATION OF DENGUE HEMMORHAGIC FEVER - YUNIKA SARI (NIM : 10108039); Pembimbing : Dr. Nuning Nuraini, MERYDA
Dengue Hemmorhagic Fever is a dangerous disease to humans caused by dengue virus. The spread of the disease is formulated into a differential equation SIRV, which is a modification of the Susceptible-Infected-Recovered (SIR) model with the adding a vaccination factor. In this model, the mosquito as the intermediary variables is also added. Beside preventing the spread of the disease, many people doing research to find a vaccine for the prevention of endemic. Usually, the government allocate limited of funds to solve this problem, therefore optimization methods are needed to determine the minimum cost to give vaccine for the people. The optimization method is formulated in the objective function, as cost function. The model is a quadratic equation with a the number of epidemic in a population as a constrains. The solution of this problem is obtained by combining Runge Kutta orde 4 and the genetic algorithm methods. The value of minimum cost function will be analyzed to get the proper vaccination proportion to solve this problem.